FAKTOR-FAKTOR YANG MEMPENGARUHI KEPATUHAN SUKARELA WAJIB PAJAK - Rahayu, Dewi Pudji (Jurnal Akuntansi Indonesia, 2019)
The aim of this research is finding factors affect voluntary compliance. These factors consist of tax knowledge, tax spent tranparency, and tax fairness. Samples of this reasearch are Personal Tax Payers who attend to submit monthly Tax Return at Jakarta Kebayoran Dua Tax Office. Results of this research are that tax knowledge of tax payers, tax spent tranparency, and tax fairness have significant effect toward voluntary compliance partially and together.